Tanggung Jawab Pemerintah dalam Pemenuhan Hak Konstitusional Atas Hak Pendidikan di Masa Pandemi Covid-19: Government Responsibilities in Fulfilling Constitutional Rights to Education Rights during the Covid-19 Pandemic - Ayuningthyas, Nadya Indah; Imanullah, Muhammad Alfin; Permana, Aulia Anastasya Putri (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
Fulfilling access to education is the main responsibility of the state and this has been stated in the Preamble to the 1945 Constitution and Articles 31 and 32 of the 1945 Constitution. This is because the right to education is a means to fulfill other rights. However, with the Covid-19 outbreak, the fulfillment of the right to education will be hampered. Based on survey data conducted by UNICEF on 18-29 May 2020 and 5-8 June 2020 in 34 provinces of Indonesia with responses from 4,000 students through the U-Report channel consisting of SMS, WhatsApp, and Messenger related to the experience of students studying from home during their period of time. The Covid-19 pandemic stated that as many as 38 percent of students felt that they lacked guidance from teachers. The unequal technology infrastructure is felt by 35 percent of students. If distance learning continues, more than half or 62 percent of respondents admit that they need internet quota. For this reason, it is very important for the government to prioritize the handling of PJJ problems to realize the right to education as mandated by the constitution. This article will explain the constitutional guarantee of the right to education during the Covid-19 pandemic. As well as, the government's responsibility in fulfilling constitutional rights to education rights during the Covid-19 pandemic. The government has the obligation to provide quality education in accordance with religious values and Pancasila as an effort to realize the state's goal of educating the nation's life as stated in the 1945 Constitution, paragraph 4. The rights to education are regulated in Article 31 of the 1945 Constitution where every citizen has the right to have the opportunity to improve lifelong education. Especially during this COVID-19 pandemic, the fulfillment of education must continue because world developments continue if only because the Covid-19 pandemic situation stops the fulfillment of education, it will have an impact on the welfare of the people. The research method used in this paper is juridical legal research, which is legal research that bases its analysis on applicable laws and regulations and is relevant to legal issues that are the focus of research and uses library research data collection techniques. This paper concludes that Distance Learning (PJJ) is one of the mandatory learning methods during the pandemic even though it is considered ineffective by looking at all the obstacles in Distance Learning (PJJ) such as limited internet quotas, devices, signals, and difficulties in related subjects. with practices. The existence of a face-to-face learning method policy in the new normal period is an effort by the government to fulfill the constitutional right to public education, but the government must be able to take full responsibility for the implementation of health protocols in the face-to-face learning process in the new normal era.